2011
DOI: 10.1109/tcomm.2011.121410.100149
|View full text |Cite
|
Sign up to set email alerts
|

Space-Time Block Coded Spatial Modulation

Abstract: Email\ud Print\ud Request Permissions\ud A novel multiple-input multiple-output (MIMO) transmission scheme, called space-time block coded spatial modulation (STBC-SM), is proposed. It combines spatial modulation (SM) and space-time block coding (STBC) to take advantage of the benefits of both while avoiding their drawbacks. In the STBC-SM scheme, the transmitted information symbols are expanded not only to the space and time domains but also to the spatial (antenna) domain which corresponds to the on/off statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
333
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(340 citation statements)
references
References 21 publications
3
333
0
4
Order By: Relevance
“…Moreover, the single-RF design is capable of employing a low-complexity single-stream maximum-likelihood (ML) detector and offering an increased energy efficiency compared with multiple-RF-chain-based schemes. As a result, SM constitutes a promising transmission candidate for multiple-input-multiple-output (MIMO) design [7][8][9]. It is found that the performances (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the single-RF design is capable of employing a low-complexity single-stream maximum-likelihood (ML) detector and offering an increased energy efficiency compared with multiple-RF-chain-based schemes. As a result, SM constitutes a promising transmission candidate for multiple-input-multiple-output (MIMO) design [7][8][9]. It is found that the performances (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…SM can also be combined with other MIMO technologies such as the space-time coding. Related research works were reported in [21]- [23]. Beside radio frequency wireless communications, SM has also been used in optical wireless communication systems [24], [25].…”
mentioning
confidence: 99%
“…STBC-CSM). The proposed STBC-CSM scheme was shown to increase spectral efficiency with the help of the extended code set when compared to the pioneering design in [6], resulting in higher spectral efficiencies even when employing fewer transmit antennas. Moreover, the STBC-CSM scheme has achieved considerable coding gain distances (CGDs) between the available CWs that pave the way for operating at lower bit error rates (BERs) when compared to the H-STBC-SM and CIOD-SM-H schemes and at nearly the same BERs as the STBC-SM.…”
Section: Introductionmentioning
confidence: 98%